A comprehensive approach to classify reactive power consumption in transmission technologies - Höhn, Sebastian; Semerow, Anatoli; Luther, Matthias (International Conference on Renewable Energies and Power Quality (ICREPQ13), 2013)
Reactive power consumption is an essential feature of any electrical equipment applied in electrical power systems. To accomplish its main task, i.e. the transfer of active power, an electrical device interacts with the system it is connected to. A common aim is to reduce the reactive power flow on the terminals of the equipment to a minimum. Therefore it’s necessary to compensate the reactive power consumption by means of adequate measures. This can’t be reached without precise investigation on the sources of reactive power emergence. This paper investigates the physical phenomena underlying the reactive power behavior of HVAC and HVDC transmission technologies. After having introduced a common mathematical definition of active, apparent and reactive power, reactive power is categorized and the concept is applied to analyze the aforementioned technologie
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.leen.acompr
Keywords: HVDC; HVAC; reactive power; power quality; converter technology

A Contribution to Thorough Comprehension of POD Provided by FACTS Devices - Höhn, Sebastian; Luther, Matthias; Graber, Thomas (Proceedings of International ETG Congress 2015; Die Energiewende - Blueprints for the new energy age, 2015)
UnivIS-Import:2017-01-09:Pub.2015.tech.IE.leen.acontr

An Innovative Method to Develop Power System Equivalents with Focus on Inter-Area Oscillations and Primary Control Representation - Semerow, Anatoli; Höhn, Sebastian; Bauer, Benedikt; Luther, Matthias (PowerTech2015, 2015)
UnivIS-Import:2015-07-08:Pub.2015.tech.IE.leen.aninno

Comparison of Transmission Technologies with Regard to their Contribution to Power System Stability - Höhn, Sebastian; Semerow, Anatoli; Luther, Matthias (International Conference on Renewable Energies and Power Quality (ICREPQ15), 2015)
UnivIS-Import:2015-04-17:Pub.2015.tech.IE.leen.compar

Dynamic Study Model for the Interconnected Power System of Continental Europe in Different Simulation Tools - Semerow, Anatoli; Höhn, Sebastian; Luther, Matthias; Sattinger, Walter; Abildgaard, Hans; Diaz, Garcia Agustin; Giannuzzi, Giorgio (PowerTech2015, 2015)
UnivIS-Import:2015-07-08:Pub.2015.tech.IE.leen.dynami

Generator Modeling in the Context of Small-Signal Stability - Kreplin, Sarina; Höhn, Sebastian; Semerow, Anatoli; Luther, Matthias (Proceedings on IEEE PES General Meeting 2016, 2016)
UnivIS-Import:2017-01-09:Pub.2016.tech.IE.leen.genera_8
Keywords: Generator Modeling; Inter-Area Oscillations; Modal Analysis; Small-Signal Stability

Impact of Load Modeling on Small Signal Stability Investigations - Wellhöfer, Sabine; Luther, Matthias; Höhn, Sebastian (International Conference on Power Systems Technology (Powercon), 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IE.leen.impact_6
Keywords: damping; eigenvalues; load modeling; modal analysis; single-machine infinite-bus system; small signal stability

Methodology for state-space modelling of power electronic elements in modern electrical energy systems - Patino, M; Höhn, Sebastian; Dimitrovski, Robert (15th International Conference on AC and DC Power Transmission, 2019)